Variability in body temperature in healthy adults and in patients receiving chemotherapy: prospective observational cohort study - Frazer, JS; Barnes, GE; Woodcock, V; Flanagan, E; Littlewood, T; Stevens, RJ; Fleming, S; Ashdown, HF (Taylor and Francis, 2020)
Between-individual variability of body temperature has been little investigated, but is of clinical importance: for example, in detection of neutropenic sepsis during chemotherapy. We studied within-person and between-person variability in temperature in healthy adults and those receiving chemotherapy using a prospective observational design involving 29 healthy participants and 23 patients undergoing chemotherapy. Primary outcome was oral temperature. We calculated each patient’s mean temperature, standard deviation within each patient (within-person variability), and between patients (between-person variability). Secondary analysis explored temperature changes in the three days before admission for neutropenic sepsis. 1,755 temperature readings were returned by healthy participants and 1,765 by chemotherapy patients. Mean participant temperature was 36.16 C (95% CI 36.07–36.26) in healthy participants and 36.32 C (95% CI 36.18–36.46) in chemotherapy patients. Healthy participant within-person variability was 0.40 C (95% CI 0.36–0.44) and between-person variability was 0.26 C (95% CI 0.16–0.35). Chemotherapy patient within-person variability was 0.39 C (95% CI 0.34–0.44) and between-person variability was 0.34 C (95% CI 0.26–0.48). Thus, use of a population mean rather than personalised baselines is probably sufficient for most clinical purposes as between-person variability is not large compared to within-person variability. Standardised guidance and provision of thermometers to patients might help to improve recording and guide management.